CSR and Firm Performance Nexus in UK: Empirical Evidence of Manufacturing Sector - Limones, Daniel (Journal of Accounting, Business and Finance Research, 2020)
The study aims to determine the impact of CSR on the firm performance in the context of manufacturing of UK. The study focuses on adopting the quantitative design of research, while the instrument used for the purpose of gathering the respondents is survey questionnaire. The data collected from 305 respondents working in the manufacturing sector of UK. The Smart PLS method is used for analysis. The data examines by using the measurement and path assessment model. The results indicate that there is a significant and positive impact of the corporate social responsibility on the firm performance of companies operating in manufacturing sector of UK. The study is limited to the manufacturing sector only that is operating within UK. Nevertheless, the research has various implications for the manufacturing sector of UK, and its managers and workers.